Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Makanan Cepat Saji di KFC Cabang Bukittinggi pada Mahasiswa STIE HAS Bukittinggi - Nurfitriyenni, Nurfitriyenni (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
This study aims to determine the effect of product, price, location and promotion on fast food purchasing decisions at KFC Bukittingi Branch. The population of this study were 194 students of STIE HAS Bukittinggi in 2016 and obtained a sample of 66 respondents. This data processing used SPSS 16.0 assistance. The data analysis method used in this research is the Instrument Test, namely the Validity Test and the Reliability Test, and the Variable Descriptive Analysis. The analytical tool used is the classical assumption test consisting of multicollinearity test, normality test and heteroscedasticity test. Multiple Linear Analysis, and Hypothesis Test, namely T test, F test and coefficient D. The results of data analysis show that: (X1) Product, (X2) Price, (X3) Location, (X4) Promotion has a positive and significant effect on fast food purchasing decisions at KFC Bukittinggi Branch both partially and simultaneously. , In the test the coefficient of determination of the independent variable has a strong contribution to the influence of the Bukittinggi Branch. Then the rest is influenced by other variables on the decision to buy fast food at KFC which is not included in this study.